The moderating role of recovery durations in high intensity interval training protocols of runners, cyclists and team sport athletes - Schoenmakers, P. P. J. M. (University of Essex, 2020)
High intensity interval training (HIIT) is often regarded the most effective training modality to improve cardiorespiratory and metabolic functioning, and, in turn endurance performance. HIIT incorporating repeated long work intervals (up to 16 min) can be described as `aerobic interval training` (AIT), as work intensities are undeniably high - but ultimately submaximal. Collating the results of ~80 unique AIT interventions, significant small to moderate improvements were evident in both VO2max and performance. The of results our meta-analysis further suggested that AIT improved V?O2max and performance significantly more than moderate intensity continuous training, and to a similar extent as sprint interval training. It was suggested that the time athletes spent at high percentages of VO2max (= 90% V?O2max (t90VO2max) could serve as a good criterion to judge the effectiveness of AIT protocols. Even though AIT is common practice in training regimes of (traditionally) endurance athletes, surprisingly little research has explored the overall impact and potential moderating role of recovery durations on the overall effectiveness of AIT protocols. In both runners and cyclists, we show that in a six 4 min self-paced AIT protocol (performed under `isoeffort` conditions), longer recovery intervals facilitated higher external training loads (higher running velocities/higher power outputs), whilst the internal training load in these sessions (t90VO2max) was not moderated by an increased recovery duration. In the context of a pre-season conditioning period of collegiate rugby players, we show that in AIT protocols of matched work intensities and training volume, the use of short recovery intervals (1 min) did not offer any advantage over the use of longer recovery intervals (3 min). The results of this thesis indicate, that when athletes incorporate self-paced AIT sessions in their training programs, long recovery intervals will allow athletes to train on higher external loads, which potentially triggers greater training adaptations.